Sonographic Evaluation of Urinary Bladder Wall Thickness in Healthy Adults : Urinary Bladder Wall Thickness in Healthy Adults - Zafar, Aiman; John, Akash; Ali, Abid; Ansar, Arooj; Ashfaq, Nayyar (Pakistan Journal of Health Sciences, 2022)
The urinary bladder is distensible empty viscous with thick muscular walls organ in the pelvis. For normal urination the wall thickness of the bladder should be normal in the range. Objective: To determine urinary bladder wall thickness using ultrasound in normal adults. Methods: It was a cross-sectional study conducted over 4 months from December 2021 to March 2022 in the private sector hospital in Gujranwala, Pakistan. A sample size of 60 was collected using the convenient sampling approach from taking mean of sample sizes of previous related study. Participants with no disease were included after informed consent. Data were analyzed and entered using SPSS version 20.0. Results: The mean age of participants was 33.41 ± 11.9, the mean weight was 75.51 ± 13.9 and height was 171.08 ± 12.5. The mean body mass index was 25.00 ± 3.9. The mean of anterior wall thickness was 2.85 ± 0.405 and posterior wall thickness was 2.86 ± 0.430. Regarding lateral wall thickness, mean right lateral was 2.78 ± 0.464 and left lateral was 2.80 ± 0.430. The participants categorized into normal, overweight and obese showed very slight differences in the mean values of anterior, posterior and lateral wall thickness of bladder. Conclusion: In conclusion, ultrasound is the best modality for measuring the wall thickness of the urinary bladder in both males and females. The age and gender do not affect BWT. A small change is noted in thickness of anterior, posterior and lateral walls of urinary bladder.